(3eLehYI aj GdgfOSIs ((3GHf eMehO Hf eMeO GdchHGFi s)
(3ChdgG (B:s
(3GdMeO ddg eHOY GdMbGFb GdNGQLI Yf GdMUQ hbO cfJ YedJ ajeG eVi ef GdReGf cJGHkG LGeYkG dVHW OYGhi GdTcd hcGf Pdc GdcJGH HGddSGf GdaGQSi aSCdfi HYV GdCUObGA ef WdHI GdYde Cf Cfbdg Zdi dGdSGf GdYQHi s
(3BNQgG (B:s
(3hdfbWY GdcdGe ggfG MGeOjf Gddg Ydi GdGFI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGef YTQs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3Jdjg ebGdI dKGHJ Hf bQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs